2017
DOI: 10.16965/ijpr.2017.119
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Awareness in Medical and Non Medical Population: A Social Media Survey

Abstract: Background: Physiotherapy is one of the oldest branches of healthcare profession which is concerned with holistically rehabilitating the patient. In recent years, the field has evolved rapidly providing evidence based quality health services. Inspite of people awailing physiotherapy services its awareness to a certain extent appears to be less. The purpose of this study was to find level of awareness of Physiotherapy among medical professionals and general population. Materials and Methods:A semi structured, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 1 publication
2
15
0
Order By: Relevance
“…In present study, only 34.7% non medical professionals were aware that human papilloma virus (HPV) is a cause for oral cancer; whereas it is known that oropharyngeal cancer is strongly associated with post treatment. These findings were correlated with study conducted Doshi D et al where in participants among the general population were surveyed and the results obtained were on the same lines with the current study; the study concluded that there need to create more awareness about the specialties in the field of physiotherapy [5]. Meurman J [9] found that Candida albicans is a commonly isolated yeast in the oral cavity that is seen particularly among medically compromised patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In present study, only 34.7% non medical professionals were aware that human papilloma virus (HPV) is a cause for oral cancer; whereas it is known that oropharyngeal cancer is strongly associated with post treatment. These findings were correlated with study conducted Doshi D et al where in participants among the general population were surveyed and the results obtained were on the same lines with the current study; the study concluded that there need to create more awareness about the specialties in the field of physiotherapy [5]. Meurman J [9] found that Candida albicans is a commonly isolated yeast in the oral cavity that is seen particularly among medically compromised patients.…”
Section: Discussionsupporting
confidence: 90%
“…It's known that knowledge of physiotherapy utilization as a treatment option in the field of musculoskeletal, neurosciences, and sports is adequate, whereas in fields like plastic surgery, oncology, gynecology & obstetrics is quite poor [5]. Therefore, the present study recruited non medical professionals to assess the perception and knowledge regarding role of physiotherapy in oral/mouth cancer survivors, and the major results of the present study shows that maximum non medical professionals had knowledge regarding integrating physiotherapy services in treating problems faced by oral cancer survivors, since there was no data available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found future colleagues' base knowledge and favorable attitude as key components for more interdisciplinary co-operations. [ 26 27 28 ] Our qualitative result, “If you want to extend the boundaries of professional communications with physicians, you should interfere the physicians in training curriculum which impress most their future decisions,” is in line with the existed studies.…”
Section: Discussionsupporting
confidence: 66%
“…Likewise, a study conducted to find awareness among high school students concluded that not much awareness regarding physiotherapy career is there 13 . In addition, it was found that measures are required to improve awareness regarding physiotherapy 14 .…”
Section: Discussionmentioning
confidence: 99%